Semiconducting Small Molecules as Active Materials for p‐Type Accumulation Mode Organic Electrochemical Transistors. (15th May 2020) - Parr, Zachary S.; Rashid, Reem B.; Paulsen, Bryan D.; Poggi, Benjamin; Tan, Ellasia; Freeley, Mark; Palma, Matteo; Abrahams, Isaac; Rivnay, Jonathan; Nielsen, Christian B.
Abstract: A series of semiconducting small molecules with bithiophene or bis‐3, 4‐ethylenedioxythiophene cores are designed and synthesized. The molecules display stable reversible oxidation in solution and can be reversibly oxidized in the solid state with aqueous electrolyte when functionalized with polar triethylene glycol side chains. Evidence of promising ion injection properties observed with cyclic voltammetry is complemented by strong electrochromism probed by spectroelectrochemistry. Blending these molecules with high molecular weight polyethylene oxide (PEO) is found to improve both ion injection and thin film stability. The molecules and their corresponding PEO blends are investigated as active layers in organic electrochemical transistors (OECTs). For the most promising molecule:polymer blend (P4E4:PEO), p‐type accumulation mode OECTs with µA drain currents, μS peak transconductances, and a µC* figure‐of‐merit value of 0.81 F V −1 cm −1 s −1 are obtained. Abstract : Mixed ionic–electronic conduction is demonstrated for a p‐type small molecule through rational molecular design. The mixed conduction is evaluated using an organic electrochemical transistor thus affording a µC* figure‐of‐merit value of 0.81 F V −1 cm −1 s −1 when the best performing molecule is blended with 10 wt% high molecular weight polyethylene oxide.